Evaluation of the Overcoming Program for Malnutrition in the Work Area of the Benteng Jawa Community Health Center, Lamba Leda District, East Manggarai Regency - Afri, Lasarus; Basri, Muntasir; Kenjam, Yoseph (Timorese Journal of Public Health, 2020)
The number of under-nutrition children under five in the work area of ​​the Bentng Jawa Health Center in the last 3 years, from 2017 to 2019, has always been stable at 10 people. This number shows the ineffective implementation of nutrition control programs in the work area of ​​the Benteng Jawa Health Center. This occurs due to poor management, starting from input, process and output. This study aims to evaluate the nutrition management program in the Benteng Jawa Health Center in 2019, with 10 informants. The results showed that the input, including the human resources involved in the program, was sufficient, so that there were no obstacles related to human resources. Funds for the 2019 malnutrition control program came from the Health Office's BOK funds amounting to IDR 2,400,000.The facilities and infrastructure to support program implementation are sufficient and work well. The process includes monitoring growth with a target of reaching 100%. Extension or counseling is carried out by midwives, nutrition officers, and KIA officers and is carried out every posyandu is held. Supplementary feeding is carried out every 6 months a year. Output consists of nutritional status, has fluctuated in the last 5 years, maternal knowledge is very low so that it affects baby care, and PMT coverage in 2019 is 100%. It is hoped that Puskesmas will be more creative in providing an understanding of nutrition to mothers of toddlers and the need to involve traditional and community leaders.